2021
DOI: 10.3390/agronomy11102044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Wheat Tissues on the Population Parameters of the Fall Armyworm (Spodoptera frugiperda)

Abstract: The fall armyworm (FAW), Spodoptera frugiperda, is an invasive migratory pest that prefers to feed on crops of the Gramineae family such as maize and wheat. It has been recorded in different locations in China since its invasion in 2019. To assess its effect on different wheat tissues and to provide a risk evaluation for wheat fields, FAW larvae were reared on the wheat seedling (WS), spike (SPK), peduncle (PDC), flag leaf blade (F-b), and blade of the first leaf under flag (F-1b). The population parameters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…1 While native to the Americas, 2,3 it has recently invaded Africa and Asia (https://www.cabi.org/isc/fallarmyworm), most recently spreading rapidly in China. 4 S. frugiperda has two sympatric strains, the 'corn strain' (C strain), which prefer to feed on maize and other large grasses, and the 'rice strain' (R strain) that preferentially feeds on rice and various pasture grasses, [5][6][7] yet which can all complete their entire life cycle on various plants owning to its high degree of polyphagy and adaptability. Consequently, understanding how insects adapt to their host plants is essential to develop efficient resistance management tools.…”
Section: Introductionmentioning
confidence: 99%
“…1 While native to the Americas, 2,3 it has recently invaded Africa and Asia (https://www.cabi.org/isc/fallarmyworm), most recently spreading rapidly in China. 4 S. frugiperda has two sympatric strains, the 'corn strain' (C strain), which prefer to feed on maize and other large grasses, and the 'rice strain' (R strain) that preferentially feeds on rice and various pasture grasses, [5][6][7] yet which can all complete their entire life cycle on various plants owning to its high degree of polyphagy and adaptability. Consequently, understanding how insects adapt to their host plants is essential to develop efficient resistance management tools.…”
Section: Introductionmentioning
confidence: 99%
“…We assumed that older corn leaves tended to have thicker and stiffer cell walls and thus less favoured by leaf-eating insects. The examination to wheat leaf also conducted by [17] found that wheat in seedling stage was the best food source for FAW growth, development, and reproduction (young leaves). This result in accordance with the results found in the study that the FAW damage started in to attack the leaves after 27 DAP and prefer the new leaves of plant.…”
Section: Resultsmentioning
confidence: 99%
“…The BSF reared on tofu dregs has a shorter TPOP, higher survival rate but lower fecundity compared with BSF reared on fermented maize straw 14 , vegetable and fruit waste 6 and a mixture of wheat bran with chicken feed 33 . The age of first oviposition by females (APOP and TPOP) has an important effect on reproduction status on population growth 43 .…”
Section: Resultsmentioning
confidence: 99%